Effects of maternal obesity on placental function and fetal development. Issue 3 (March 2017) - Howell, Kristy R; Powell, Theresa L
Abstract : Obesity has reached epidemic proportions, and pregnancies in obese mothers have increased risk for complications including gestational diabetes, hypertensive disorders, pre-term birth and caesarian section. Children born to obese mothers are at increased risk of obesity and metabolic disease and are susceptible to develop neuropsychiatric and cognitive disorders. Changes in placental function not only play a critical role in the development of pregnancy complications but may also be involved in linking maternal obesity to long-term health risks in the infant. Maternal adipokines, i.e., interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), leptin and adiponectin link maternal nutritional status and adipose tissue metabolism to placental function. Adipokines and metabolic hormones have direct impact on placental function by modulating placental nutrient transport. Nutrient delivery to the fetus is regulated by a complex interaction including insulin signaling, cytokine profile and insulin responsiveness, which is modulated by adiponectin and IL-1β. In addition, obese pregnant women are at risk for hypertension and preeclampsia with reduced placental vascularity and blood flow, which would restrict placental nutrient delivery to the developing fetus. These sometimes opposing signals regulating placental function may contribute to the diversity of short and long-term outcomes observed in pregnant obese women. This review focuses on the changes in adipokines and obesity-related metabolic hormones, how these factors influence placental function and fetal development to contribute to long-term metabolic and behavioral consequences of children born to obese mothers.